2016
DOI: 10.3389/fpls.2016.01443
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of New Gravitropic Mutants under Hypergravity Conditions

Abstract: Forward genetics is a powerful approach used to link genotypes and phenotypes, and mutant screening/analysis has provided deep insights into many aspects of plant physiology. Gravitropism is a tropistic response in plants, in which hypocotyls and stems sense the direction of gravity and grow upward. Previous studies of gravitropic mutants have suggested that shoot endodermal cells in Arabidopsis stems and hypocotyls are capable of sensing gravity (i.e., statocytes). In the present study, we report a new screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
(69 reference statements)
0
3
0
1
Order By: Relevance
“…Enhanced gravitropism by hypergravity (hyper-gravitropism) is reported in Arabidopsis roots 32 , stems 33 and hypocotyls 34 . The analysis of the plant growth under the sequential hypergravity conditions (30–500 g for 1 day) shows that hypergravity suppressed elongation growth of hypocotyls, but this effect was reduced in hypocotyls of mca -null mutants compared with the wild type 28 , suggesting that MCAs are involved in the sensing of gravity signals in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced gravitropism by hypergravity (hyper-gravitropism) is reported in Arabidopsis roots 32 , stems 33 and hypocotyls 34 . The analysis of the plant growth under the sequential hypergravity conditions (30–500 g for 1 day) shows that hypergravity suppressed elongation growth of hypocotyls, but this effect was reduced in hypocotyls of mca -null mutants compared with the wild type 28 , suggesting that MCAs are involved in the sensing of gravity signals in plants.…”
Section: Discussionmentioning
confidence: 99%
“…This makes centrifugation a useful technique to investigate the relationship between amyloplast dynamics and gravity sensing (Toyota et al 2014). Indeed, the reduced gravitropic sensitivities in pgm and sgr mutants were restored by centrifugal hypergravity (Fitzelle and Kiss 2001;Mori et al 2016;, which correlated with the resumption of amyloplast sedimentation (Fitzelle and Kiss 2001;Toyota et al 2013b). These studies suggested that intracellular distribution of amyloplasts toward the gravity vector is critical for gravity perception in plants.…”
Section: Introductionmentioning
confidence: 99%
“…This makes centrifugation a useful technique to investigate the relationship between amyloplast dynamics and gravity sensing (Toyota et al 2014). Indeed, the reduced gravitropic sensitivities in pgm and sgr mutants were restored by centrifugal hypergravity (Fitzelle and Kiss 2001; Toyota et al 2014; Mori et al 2016), which correlated with the resumption of amyloplast sedimentation (Fitzelle and Kiss 2001; Toyota et al 2013b). These studies suggested that intracellular distribution of amyloplasts toward the gravity vector is critical for gravity perception in plants.…”
Section: Introductionmentioning
confidence: 99%